Ellipsis : Functional Heads, Licensing, and Identification. - Lobeck, Anne (Oxford University Press, 1995)
This book elaborates a theory of ellipsis that sheds new light on a well-known phenomenon, bringing it under the aegis of general and universal principles. Lobeck argues that ellipted categories in IP (VP Ellipsis), DP (N' Ellipsis), and CP (Sluicing) are empty, non-referential pronominals, subject to the same licensing and identification conditions as referential pro. She proposes that both types of empty pronominals must be licensed under head-government to satisfy the Empty Category Principle, and identified through strong agreement. In the case of ellipsis, agreement-typefeatures make the.